Aspiration of a fractured tracheostomy tube, a rare complication of tracheotomy: the factors involved in this incident and literature review - Kajai, Soufiyane; Oulghoul, Omar; Rochdi, Youssef; Raji, Abdelaziz (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Tracheostomy is executed routinely for several indications. It is a safe and life-saving procedure. In some cases, the tracheostomy tube has to be maintained for a long duration. We report a rare case of aspiration of a fractured tracheostomy tube. In the light of the literature, we reported the various factors leading to complications of tracheotomy. A 5-year-old boy, presenting to the emergency department for aspiration of a fractured tracheostomy tube accidentally during a cleaning process by his mother. On clinical examination, the patient was slightly symptomatic. A flexible bronchoscopy was made which objectified the presence of the cannula in the trachea, an additional chest X-ray was taken, which revealed the aspirated tracheostomy tube in the trachea and right main bronchus. Extraction was done by rigid bronchoscopy under general anesthesia. The postoperative course of the patient remain uneventful. In order to reduce the potentially fatal complications of the tracheotomy, it is necessary to insist on a regular medical follow-up.